2019
DOI: 10.1002/asia.201901499
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐Conductive 3D LnIII Metal–Organic Frameworks for Formic Acid Impedance Sensing

Abstract: Metal-organic frameworks (MOFs) as new classes of proton-conducting materialsh ave been highlighted in recent years. Nevertheless, the exploration of proton-conducting MOFs as formic acid sensors is extremelyl acking. Herein, we prepared two highly stable 3D isostructurall anthanide(III) MOFs, {(M(m 3 -HPhIDC)(m 2 -C 2 O 4 ) 0.5 (H 2 O))·2 H 2 O} n (M = Tb (ZZU-1); Eu (ZZU-2)) (H 3 PhIDC = 2-phenyl-1H-imidazole-4,5-dicarboxylic acid), in which the coordinated and uncoordinated water molecules and uncoordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…[1][2][3][4] Moreover, the most prominent advantage of MOFs is that their structures can be regulated and controlled during or after synthesis. 5 So far, MOFs have been widely used in catalysis, 6,7 fluorescence, [8][9][10][11][12] gas adsorption, [13][14][15] proton conduction, [16][17][18][19][20] sensors [21][22][23][24] and so on. In recent years, the research of MOFs has advanced rapidly, and thousands of MOFs have been syn- 39 They used MeOH to dissolve Bi(NO 3 ) 3 •5H 2 O and the 2-pyridinecarbaldehyde isonicotinoylhydrazone (Hpcih) ligand in the two arms of the branch tube and sealed the tube.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Moreover, the most prominent advantage of MOFs is that their structures can be regulated and controlled during or after synthesis. 5 So far, MOFs have been widely used in catalysis, 6,7 fluorescence, [8][9][10][11][12] gas adsorption, [13][14][15] proton conduction, [16][17][18][19][20] sensors [21][22][23][24] and so on. In recent years, the research of MOFs has advanced rapidly, and thousands of MOFs have been syn- 39 They used MeOH to dissolve Bi(NO 3 ) 3 •5H 2 O and the 2-pyridinecarbaldehyde isonicotinoylhydrazone (Hpcih) ligand in the two arms of the branch tube and sealed the tube.…”
Section: Introductionmentioning
confidence: 99%
“… 89 Li’s group observed the proton-conducting response to formic acid vapor in two 3D isostructural Ln(III) MOFs, ZZU-1 and ZZU-2. 90 They can distinguish formic acid vapor from other organic small-molecule vapors such as methanol, ethanol, acetone, toluene, acetic acid, etc. It may be concluded that only formic acid can form hydrogen bonds with H 2 O and imidazole, ascribed to the large polarity (in comparison with hydrocarbons, alcohols, or ketones) and small volume (in comparison with acetic acid) of formic acid.…”
Section: Guest-controlling Switchable Proton Conductivity In Metal–or...mentioning
confidence: 99%
“…Formic acid sensing was stabilized by H-bond formation between the imidazole nitrogen-linked MOFs and formic acid. [209] The better geometrical and luminescence properties of lanthanides MOFs could be due to the metal center possessing 4f-electrons. [210] Toluene is hazardous and carcinogenic, with exposure causing adverse health effects.…”
Section: Mofs Sensing Behavior Toward Organic Solventsmentioning
confidence: 99%